Biomedical Image Registration 10th International Workshop, WBIR 2022, Munich, Germany, July 10-12, 2022, Proceedings - Hering, Alessa; Schnabel, Julia; Zhang, Miaomiao; Ferrante, Enzo.; Heinrich, Mattias; Rueckert, Daniel (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book constitutes the refereed proceedings of the 10th International Workshop on Biomedical Image Registration, WBIR 2020, which was supposed to be held in Munich, Germany, in July 2022. The 11 full and poster papers together with 17 short papers included in this volume were carefully reviewed and selected from 32 submitted papers. The papers are organized in the following topical sections: optimization, deep learning architectures, neuroimaging, diffeomorphisms, uncertainty, topology and metrics.
Atlases -- Topology -- Uncertainty -- Architectures -- Optimization -- Metrics -- Losses -- Efficiency.
Keywords: Image processing-Digital techniques; Computer vision; Machine learning; Education-Data processing; Social sciences-Data processing; Bioinformatics; Computer Imaging, Vision, Pattern Recognition and Graphics; Machine Learning; Computers and Education; Computer Application in Social and Behavioral Sciences; Computational and Systems Biology